Designing of the Software Program “Epidemic Potential of Natural Plague Foci in the Territory of the Russian Federation” - E. V. Kouklev; V. A. Safronov; A. A. Lopatin; A. S. Razdorsky (Проблемы особо опасных инфекций, 2014)
Designed has been a computer program “Epidemic potential of natural plague foci in the Russian Federation” applied for the automatized evaluation of the epidemic hazard level of natural plague foci in relation to the population residing on the territory of them. This software optimizes management decision making via provision of the Heads of the Rospotrebnadzor organizations with the comprehensive current data on the sanitary-epidemiological situation on plague across the whole territory of the natural foci in Russia, and by enhancing the quality of the visual data display, which are essential for the decision making in the sphere of biological safety provision. In consequence of integration into “Deductor” software program, counted value of epidemic potential for any location of the natural focus territory can be ranked correspondently using colorimetric scale (from red up violet color, for maximum and minimum rating, respectively). The program is designed on the base of Arc GIS Platform to be introduced into the automatized information analysis system for the provision of biological safety in the constituent entities of the Russian Federation.